UPAYA MENINGKATKAN KEMAMPUAN MENULIS TEKS EKSPOSISI DAN PRESTASI BELAJAR BAHASA INDONESIA DENGAN METODE INKUIRI KELAS X IPS 1 SEMESTER GANJIL SMA NEGERI 3 METRO - Susnelly, Susnelly (STKIP PGRI Bandar Lampung, 2021)
This study aims to describe the skills of writing exposition texts, the inquiry method of learning Indonesian for the students of class X IPS 1 SMA Negeri 3 Metro. The data analysis of this study used data analysis obtained through three stages, namely (1) data reduction (2) data presentation and (3) conclusion drawing (data verification). Sources of data obtained from primary data and secondary data. Tools and data collection with test and non-test techniques. The results and discussion of the ability to write exposition texts for students of class X IPS 1 SMA Negeri 3 Metro can be explained as follows: 1) ability to write text structure, 2) language characteristics, 3) text content, 4) written expressions, and 5) mechanics/spelling used. The process of writing exposition text skills from pre-cycle, cycle I, cycle II, and cycle III increased significantly. While learning achievement has increased, this is from the average pre-cycle result, which was 46% in the first cycle, to 66%. Cycle II to 75%, cycle III increased to 80% of class X IPS 1 students at SMA Negeri 3 Metro for the 2017/2018 academic year. Mastery learning in the pre-cycle is still 0, in the first cycle there are 10 people (31.25%), the second cycle 19 people (59.37%) and the third cycle 32 people (100%).